ANALISIS IMPLEMENTASI STRATEGI PERENCANAAN PAJAK (TAX PLANNING) SEBAGAI UPAYA PENGHEMATAN BEBAN PAJAK PENGHASILAN: Studi Kasus Pada CV XYX - Dyni Annisa Faradilla; Rizki Filhayati Rambe (Universitas Methodist Indonesia, 2022)
This research aims to analyze the implementation of a tax planning strategy to save corporate income tax in CV XYZ. This research used the descriptive qualitative method. Data collection techniques through documentation, interviews, and literature. Data analysis by analyzing the commercial financial statement, reconciling fiscal, analyzing fiscal income statement, and making tax planning. The results of this study are CV XYZ has implemented tax planning in financial statements, however, it has not been optimally, resulting in only minor savings. The implementation of the tax planning through directing the president director's personal advertising expense becomes the company's advertising expense only.